2018
DOI: 10.1108/ijhcqa-08-2017-0149
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of an in-hospital stroke simulation protocol

Abstract: Purpose A major component of hospital stroke care involves prompt identification of stroke in admitted patients. Delays in recognizing stroke symptoms and initiating treatment for in-hospital stroke can adversely impact patient outcomes. This quality improvement intervention used simulation together with a traditional lecture to instruct nurses at a university hospital about a new stroke protocol being implemented to increase rapid recognition of stroke and meet Joint Commission National Hospital Inpatient Qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 22 publications
0
6
0
1
Order By: Relevance
“…This is an area in which improved education with a variety of tools such as simulation laboratories might improve recognition and diagnosis. 51…”
Section: Challenges Limitations and Stroke Systems Of Carementioning
confidence: 99%
See 1 more Smart Citation
“…This is an area in which improved education with a variety of tools such as simulation laboratories might improve recognition and diagnosis. 51…”
Section: Challenges Limitations and Stroke Systems Of Carementioning
confidence: 99%
“…This is an area in which improved education with a variety of tools such as simulation laboratories might improve recognition and diagnosis. 51 Nurses are often the first hospital staff to recognize a patient with symptoms that might indicate in-hospital stroke and activate a stroke alert. Nurses activate inhospital stroke alerts significantly earlier than physicians or advanced practice clinicians (median, 2.0 hours versus 4.9 hours) from last known well time, with median nursing activation time falling within a 3-hour window for potential systemic thrombolytic or early endovascular therapy.…”
Section: Challenges Limitations and Stroke Systems Of Carementioning
confidence: 99%
“…Additionally, many studies performed local (in situ) simulation,9 20 while our simulation was done centrally in an equipped simulation centre. Finally, some studies did not measure patient-relevant outcomes, but instead measured an improvement in knowledge 19 26 27. Nevertheless, two previously published studies from Germany and Norway20 21 and our study document that simulation training contributes to a short final DNT.…”
Section: Discussionmentioning
confidence: 58%
“…In terms of education and training, simulation-based learning using standardized patients may improve nurses' ability to identify stroke symptoms. 33 A study by Mellon et al 34 found that while some staff could identify symptoms of stroke, they were unaware of treatment windows for thrombolytic therapy. This knowledge gap emphasizes the need for staff education focused on both symptom recognition and appropriate treatment protocols.…”
Section: Snavely and Thompsonmentioning
confidence: 99%